2016
DOI: 10.1097/brs.0000000000001909
|View full text |Cite
|
Sign up to set email alerts
|

Propionibacterium acnes, Coagulase-Negative Staphylococcus, and the “Biofilm-like” Intervertebral Disc

Abstract: Study Design.Patients scheduled for spinal surgery were screened prospectively for a microbial presence associated with intervertebral disc specimens. Inclusion was limited to patients requiring surgery for any of five conditions: study patients with cervical spine intervertebral herniation (IVH), lumbar spine IVH, lumbar spine discogenic pain, and control patients with idiopathic scoliosis/Scheurermann's kyphosis or trauma/neuromuscular deformity. Exclusion criteria included ongoing systemic infection, abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
2
5

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 36 publications
5
38
2
5
Order By: Relevance
“…McLorinan et al identified P. acnes using immunofluorescence microscopy, but they found that the bacteria colonized as single cells more than in large aggregates so the immune-labeled P. acnes was attributed as contamination [13]. Recently, Coscia et al examined degenerated intervertebral discs with Gram-staining, but none of the samples had any visible microorganisms [2]. …”
Section: Discussionmentioning
confidence: 99%
“…McLorinan et al identified P. acnes using immunofluorescence microscopy, but they found that the bacteria colonized as single cells more than in large aggregates so the immune-labeled P. acnes was attributed as contamination [13]. Recently, Coscia et al examined degenerated intervertebral discs with Gram-staining, but none of the samples had any visible microorganisms [2]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, long-term antibiotics targeting anaerobes may improve lower back pain in those with disc herniation and vertebral edema [22]. Despite this, however, other studies have failed to correlate P. acnes prevalence with LDH pathology [29]. While it is likely that P. acnes may play a role in LDH symptomology and ultimately be a target for non-operative treatment, further research must be done to elucidate the measure of effect this bacteria has on symptomatic LDH.…”
Section: Propionibacterium Acnesmentioning
confidence: 99%
“…These findings are in line with the microscopy results of the current study. Staphylococcus , specifically S. epidermis is one of the most prevalent organisms cultured from LDH . Given the high prevalence of S. epidermidis by PCR in the current study, it is not unlikely that the aggregates observed in Figs and may be S. epidermidis .…”
Section: Discussionmentioning
confidence: 72%
“…Coscia et al. examined a large series of patients using light microscopy of gram‐stained formalin‐fixated tissue section. The study found no evidence of microorganisms or chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation